2013
DOI: 10.1016/j.jss.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Towards innovation measurement in the software industry

Abstract: Context: In today's highly competitive business environment, shortened product and technology life-cycles, it is critical for software industry to continuously innovate. To help an organisation to achieve this goal, a better understanding and control of the activities and determinants of innovation is required. This can be achieved through innovation measurement initiative which assesses innovation capability, output and performance.Objective: This study explores definitions of innovation, innovation measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
175
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 115 publications
(227 reference statements)
0
175
0
21
Order By: Relevance
“…However, measuring that value using key performance indicators is a daunting challenge. Edison et al (2013) confirmed a limited number of measurement models, and that the existing ones neither model all innovation aspects, nor say what metric can be used to measure a certain aspect. Furthermore, existing literature is scarce in regards to how data should be gathered and used for the metrics proposed in the literature.…”
Section: Innovation Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, measuring that value using key performance indicators is a daunting challenge. Edison et al (2013) confirmed a limited number of measurement models, and that the existing ones neither model all innovation aspects, nor say what metric can be used to measure a certain aspect. Furthermore, existing literature is scarce in regards to how data should be gathered and used for the metrics proposed in the literature.…”
Section: Innovation Outcomesmentioning
confidence: 93%
“…Another benefit is the free maintenance and bug corrections and the test cases extension for further quality assurance. By extension, these software improvements may be labeled as product innovations depending on what definition to be used (Edison et al 2013). This may also be viewed from the process innovation perspective (OECD 2005) as Sony Mobile gets access to extra work force and a broad variety of competencies, which are internally unavailable (Dahlander and Magnusson 2008).…”
Section: Innovation Outcomesmentioning
confidence: 99%
“…The study conducted by West and Bogers [61] could be considered partly systematic, since the relevance can be seen in terms of data sources, inclusion/exclusion criteria and data extraction. On the other hand, the review conducted by Edison et al [17] adheres to Kitchenham et al [35] and Petersen at al. [45] guidelines.…”
Section: Related Workmentioning
confidence: 98%
“…We identified four secondary studies (literature reviews) [17,29,61,66] on open innovation, relevant to this study, by applying forward snowball sampling, using the study by West and Bogers [61] as a baseline. The studies are summarized in Table 1.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation